Utilization of the fish ladder at the Engenheiro Sergio Motta Dam, Brazil, by long distance migrating potamodromous species - Makrakis,Sérgio (2007)
Utilization of the fish ladder installed at the Engenheiro Sergio Motta Dam (also known as Porto Primavera) on the Paraná River, Southern Brazil, by long-distance migrating potamodromous species (sampling Protocol I), and ascending and descending movements (Protocol II) were evaluated. Three pools along the fish ladder (designated as lower, middle, and upper) were sampled monthly between December, 2004 and March, 2005 to determine the abundance of species in the ladder. The ascending and descending movements of the species in the ladder were also analyzed in the same period. In the samples for both protocols, 37 species representing 17 families and 5 orders (Characiformes, Siluriformes, Perciformes, Gymnotiformes, and Myliobatiformes) were recorded. Characiformes were represented by 21 species. Long- distance migratory species (11 species) predominated in the ladder (60% of the total number of individuals), with high abundance of Rhinelepis aspera (5645 individuals). For protocol I, mean abundance varied greatly among the months and pools, with lowest values in December and March for all pools, and highest in January for the lower pool due to high capture of R. aspera. Fish abundance declined from the lower to the upper pool, especially for R. aspera and Rhaphiodon vulpinus. For Protocol II, 17 species were recorded ascending the ladder, where Astyanax altiparanae and Leporinus friderici were the most abundant species (684 and 111 individuals, respectively). However, 18 species showed descending movements, with high captures of Metynnis maculatus and A. altiparanae (339 and 319 individuals, respectively). Twelve species (52%) moved in both directions, and among the seven migratory species sampled, four were recorded ascending and descending, and three species only ascending the ladder. The fish ladder appears to selectively favor species with high swimming capabilities. A discussion is presented on the requirements for future research on attraction to the fish ladder entrance, downstream movements, fish utilization of the ladder, and impacts on spawning and rearing habitat both upstream and downstream of the dam.